Analysis of a Proton Exchange Membrane Fuel Cell (PEMFC) for Green Hydrogen Vehicles - Ahmed, Khadhraoui; Henry, Trujillo; Adolfo, Iulianelli (Clean Energy Technologies, 2025)
This work presents the development of a hydrogen‑based green energy system for powering fuel cell electric vehicles (FCEVs), with a specific focus on sustainable urban transportation. Current battery‑electric vehicles still face persistent challenges, primarily related to high manufacturing cost, limited driving autonomy, and the need for extensive charging infrastructure. To overcome these limitations, a novel prototype was designed and implemented, integrating an autonomous hydrogen production unit directly within the vehicle. The system is supported by photovoltaic sources for renewable energy input and Lithium‑ion batteries for efficient storage and operational stability. The hydrogen produced on board is utilized by a reversible Proton Exchange Membrane Fuel Cell (PEMFC), which converts the chemical energy into electricity to drive the vehicle’s engine and supply auxiliary systems. This integrated approach ensures continuous energy availability while minimizing dependence on external charging stations. The proposed concept demonstrates several advantages, including extended driving range, reduced refueling time, increased system autonomy, and zero carbon dioxide emissions. Moreover, the design contributes to urban air quality improvement and aligns with Circular Economy (CE) protocols by promoting renewable integration and resource efficiency. Overall, the study highlights hydrogen‑based embedded systems as a promising pathway towards clean, sustainable, and resilient mobility solutions.